Compensation claims after knee arthroplasty surgery in Norway 2008–2018 - Per-Henrik Randsborg; Tommy Frøseth Aae; Ida Rashida Khan Bukholm; Anne Marie Fenstad; Ove Furnes; Rune Bruhn Jakobsen (Acta Orthopaedica, 2021)
Background and purpose — Orthopedic surgery is one of the specialties with most compensation claims. We assessed the claims following knee arthroplasty surgery reported to the Norwegian System of Patient Injury Compensation (NPE) in light of institutional procedure volume. Patients and methods — We collected data from NPE and the Norwegian Arthroplasty Register (NAR) for the study period (2008–2018). Age, sex, type of claim, and reason for compensation were collected from NPE, while the number of arthroplasty surgeries was collected from NAR. The treating hospitals were grouped by quartiles according to annual procedure volume. The effect of hospital volume on the likelihood of an accepted claim was estimated. Results — NAR received 64,241 reports of arthroplasty procedures, of which 572 (0.9%) patients filed a claim for treatment injury. 55% of the claims were accepted, representing 0.5% of all knee arthroplasties. The most common reason for accepted claim was a hospital-acquired infection, in 28% of the patients, followed by misplaced implant (26%) and aseptic loosening (13%). The hospitals with the lowest annual volume (57 or fewer arthroplasties per year, first quarter) had a statistically significantly larger fraction of granted claims per procedures compared with other institutions. Interpretation — The overall risk of ending up with compensation due to treatment error following knee arthroplasty was 0.5%. The risk of accepted claim was greater for patients operated in the lowest volume hospitals.